Arabic Language Variation and Social Identity in Arabic-Speaking Communities - Azmalia Anastasya Marcella; Nasiruddin Nasiruddin (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
This study aims to analyze the relationship between language and social identity among Arabic speakers through a sociolinguistic approach. The research is qualitative and descriptive in nature, employing a case study approach. The research subjects consist of Arabic speakers from various social backgrounds, ages, and educational levels, while the object of the study is the use of Arabic, both fusha and local dialects, in formal and informal contexts. Data were collected through in-depth interviews, participant observation, and documentation of social interactions, and analyzed using thematic and interpretative techniques to identify patterns of language use and their relationship to social identity formation. The findings reveal that Arabic speakers adjust their language variety according to the communication context, interaction goals, and social status, making language a dynamic medium for negotiating social identity. Fusha is used in formal and institutional contexts to convey authority and legitimacy, whereas local dialects are employed in everyday interactions to foster solidarity and social closeness. These results confirm that language is not merely a system of communication but a social practice that reflects social structures and cultural values. The implications of this study highlight the importance of understanding the relationship between language and social identity in Arabic language teaching, enabling more contextual, adaptive, and effective intercultural communication competence.